Assembling of Supramolecular Capsules with Resorcin[4]arene and Calix[n]arene Building Blocks - M. A. Gangemi, Chiara; Pappalardo, Andrea; Trusso Sfrazzetto, Giuseppe (Current Organic Chemistry, 2015)
Molecular capsules are containers endowed with isolated nanometer-sized cavities. In particular, supramolecular capsules -generated by exploiting hydrogen bonds, metal-coordination bonds and/or hydrophobic effects- represent an intriguing version of these fascinating molecules, and an impressive challenge for synthetic chemists. Resorcin[4]arene-based cavitands and conformationally preorganized calixarenes are two classes of receptors largely used as building blocks for the construction of these assemblies. This review focuses on the capsular self-assembly of suitably functionalized building blocks, analyzing from time to time the main driving force(s) involved for their formation.
Keywords: resorcin[4]arene